Scaling of Climate-Smart Village approach reaches next level in India and Nepal. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The climate-smart village approach is increasingly being scaled with public and private investments. Bihar Government is investing 42 M-USD in raising the capacity of stakeholders. In Nepal, provincial governments are implementing the CSV approach in 212 villages with investments of 5.5 M-USD. The federal government of Nepal has endorsed CSV approach and is establishing 200 CSVs as part of its second Nationally Determined Contributions (NDC). ITC limited aims to integrate Climate-Smart Village approach to over three million acres by 2030.